2019
DOI: 10.3390/met9101079
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Metal Velocity in Sand Casting during Mold Filling

Abstract: Melt turbulence during mold filling is detrimental to the quality of sand castings. In this research study, the authors present a novel method of embedding Internet of Things (IoT) sensors to monitor real-time melt flow velocity in sand molds during metal casting. Cavities are incorporated in sand molds to position the sensors with precise registration. Capacitive and magnetic sensors are embedded in the cavities where melt flow velocity is calculated by using an oscillator, the frequency of which is sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…It can be observed that the pouring temperature is more effect on hardness than moisture content. Moreover, hardness is maximum at the lowest level of pouring temperature because porosity and gas shrinkages defects are minimum at a lower temperature of melt, as reported in previous work [17]. However, a further rise in temperature results in a reduction of hardness, but this pattern persists up to the middle level.…”
Section: D Response Surface Plots For Hardness Uts and Srsupporting
confidence: 79%
See 2 more Smart Citations
“…It can be observed that the pouring temperature is more effect on hardness than moisture content. Moreover, hardness is maximum at the lowest level of pouring temperature because porosity and gas shrinkages defects are minimum at a lower temperature of melt, as reported in previous work [17]. However, a further rise in temperature results in a reduction of hardness, but this pattern persists up to the middle level.…”
Section: D Response Surface Plots For Hardness Uts and Srsupporting
confidence: 79%
“…Three key parameters, namely pouring temperature, pouring velocity and moisture content, were selected as the control variables in the present research. The rationale for selecting the aforesaid variables as input parameters is their well proven significance with respect to the mechanical and surface properties of the castings [9,17,18]. The control settings of the said parameters were achieved in the following manner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sensing and control model could be interfaced during casting part with multiple sensors such capacitive or magnetic sensors used to measure the melt flow velocity in mold cavities (Sama et al 2019b) and wireless sensors for temperature measurements at several deeps inside molds (Walker et al 2018). These models can be used for online control of the filling process.…”
Section: Model Update Trainingmentioning
confidence: 99%
“…Since the kinematic viscosity of most liquid metals is similar to water (Renukananda and Ravi 2016;Swift et al 1949), numerous researchers have experimented with water models using transparent molds usually made of Acrylic (Shaikh et al 2018;Renukananda and Ravi 2016) to visualize in real time the fluid flow in molds (Juretzko and Stefanescu 2005). Newly, Sama et al (2019b) have proposed a novel method of embedded Internet of Things (IoT) sensors to monitor realtime melt flow velocity in 3D sand printing mold during metal casting.…”
Section: Introductionmentioning
confidence: 99%